British Swimming - Creating a platform for elite swim performances - Logan, A. (Applied Swimming Programme Schedule - 27th International Conference on Biomechanics in Sports, 2009)
In 2008, British Swimming (BS) restructured the World Class Programme (WCP) for swimming with the establishment of five Intensive Training Centres (ITC) throughout the United Kingdom. The aim being to provide an optimal environment for elite athletes to best prepare for winning performances at international competitions. Integral to each ITC is a sport science and medical service delivery platform whereby coaches and athletes are provided access to a comprehensive array of science and medical support within their daily training and competition environment. The purpose of this talk is to provide to you an overview of the integration and applied application of swimming sciences, by coaches, within the ITC daily training environment. Particularly, the focus will be on the processes established within the ITC to identify the best use of swimming science.